The European banking union and constitution beacon for advanced integration or death-knell for democracy? - Grundmann, Stefan 1958-; Micklitz, Hans-W. (Oxford New York Hart Publishing, 2019)
"In 2012, at the height of the sovereign debt crisis, European decision makers pushed for developing an 'ever closer union' with the formation of a European Banking Union (BU). Although it provoked widespread debate, to date there has been no coherent discussion of the political and constitutional dimensions of the European Banking Union. This important new publication fills this gap. Drawing on the expertise of recognized experts in the field, it explores banking union from legal, economic and political perspectives. It takes a four part approach; firstly setting the scene by examining the constitutional foundations of banking union. It then looks at its implications for European integration and for democracy. Finally it asks whether it might be more usefully regarded as a trade-off between integration and democracy. This is an important, timely and authoritative collection"--Provided by publisher.
The European Banking Union and Constitution - the overall challenge / Stefan Grundmann and Hans-W Micklitz -- The constitutional dimension of Banking Union / Takis Tridimas -- The thin red line between the OMT decision and the Banking Union / Alessandro Busca -- The European Banking Union and integration / Stefan Grundmann -- Banking Union and the European Economic Constitution : a brief comparison of regulatory styles in banking regulation and competition law / Heike Schweitzer -- Technocratic and centralised decision-making in the Banking Union's Single Supervisory Mechanism : can single market and Banking Union governance effectively co-exist in a post-Brexit world? / Niamh Moloney -- Single resolution board : lost and found in the thicket of EU bank regulation / Agnieszka Smoleńska -- Some reflections on the state of European democracy with regard to Banking Union and the ECB / Christoph Möllers -- The European Banking Union : a case of tempered supernaturalism? / Sergio Fabbrini and Mattia Guidi -- Prudential supervision and the European Central Bank Credit Data Registry (AnaCredit) : legal basis and democratic accountability / Federico Ferretti -- The Internal Market and the Banking Union / Hans-W. Micklitz -- Should non-participating Member States join the Banking Union? A legal perspective / Dalvinder Singh.
Keywords: European Central Bank; Banks and banking -- State supervision -- European Union countries; Banking law -- European Union countries